Synergistic effects of antimicrobial components of the human-derived composite amnion-chorion membrane on bacterial growth - Brummerhop, Alexandra Su; Lee, Chun-Teh; Weltman, Robin; Tribble, Gena D.; van der Hoeven, Ransome; Chiu, Yulun; Hong, Jianming; Wang, Bing-Yan (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionThe human-derived amnion-chorion membrane (ACM) has endogenous antimicrobial properties, which are important for preventing the colonization and survival of oral bacteria on exposed membranes. This project aimed to decipher the underlying mechanism by identifying the components of ACM that confer antibacterial properties. In addition, the antimicrobial efficacy of these identified components on oral bacteria was assessed.MethodsFour antimicrobial proteins, histone H2A/H2B, cathelicidin LL-37, lactoferrin, and lysozyme, were identified via mass spectrometry in ACM. These proteins were then assessed for their efficacy in killing Streptococcus gordonii Challis. Log-phased bacterial cells were cultured with the commercially available proteins that were identified in ACM, either individually or in combination, at different concentrations. After incubation for 8 or 24 hours, the bacteria were stained with a live/dead viability kit and analyzed via confocal microscopy.ResultsThe combination of these proteins effectively killed S. gordonii in a dose-dependent fashion after 8 or 24 hours of incubation. When each protein was tested individually, it killed S. gordonii at a much lower efficacy relative to the combinations. The synergistic effects of the antimicrobial protein combinations were also observed in both the viable cell count recovery and minimum inhibitory concentration assays.DiscussionBy shedding light on the mechanisms in the ACM’s antimicrobial property, this study may raise more awareness of the potential benefit of utilization of a membrane with endogenous antimicrobial properties in regeneration surgeries.